A Multimodal Preemptive Analgesic Protocol for Alveolar Bone Graft Surgery: Decreased Pain, Hospital Stay, and Health Care Costs. (April 2019) - Bykowski, Michael R.; Sivak, Wesley; Garland, Catharine; Cladis, Franklyn P.; Goldstein, Jesse A.; Losee, Joseph E.
Objective: To evaluate postoperative pain, hospital length of stay (LOS), and associated costs of multiple perioperative analgesic strategies following alveolar bone grafting (ABG). Design: Retrospective comparative cohort study. Setting: Tertiary care pediatric hospital. Patients/Participants: Iliac crest bone graft (ICBG) harvest techniques: "Open Harvest" (n = 22), "Trephine Only" (n = 14), or "Trephine + Pain Pump" (n = 25). Intervention: The "Open Harvest" group underwent open ICBG harvest with 3-walled osteotomies. For the other 2 treatment groups, a trephine drill was used to harvest iliac crest bone with a ropivacaine infusion pump into the hip donor site ("Trephine + Pain Pump") or without ("Trephine Only"). Patients who underwent ABG with only cadaveric allograft were analyzed as a comparison group ("No Harvest"). Main Outcomes Measures: Outcomes were planned prior to data collection: maximum pain score, hospital LOS, and associated health care costs. Results: Maximum pain scores were significantly higher in the "Open Harvest" group (7.3/10) compared to "Trephine + Pain Pump" (1.8/10; P < .0001) and "No Harvest" groups (2.8/10; P < .01). Hospital LOS decreased from 2.4 days ("Open Harvest") to 0.5 days (Trephine + Pain Pump"; P < .0001). Twelve (48%) patients from "Trephine + Pain Pump" were discharged on the day of surgery. The "Trephine + Pain Pump" saved an estimated $5336 for a unilateral ABG and $7265 for a bilateral ABG compared to "Open Harvest." Conclusions: The combined use of the trephine ICBG technique and ropivacaine infusion catheter effectively decreased pain, shortened hospital stay, and improved cost saving compared to patients who have undergone other methods of ICBG.